Effect of Annealing Temperature on Mechanical Properties of AISI 1045 Carbon Steel - Moraida Hasanah; Susilawati, Susilawati; Zahar, Intan; Mulyadi, Yadi; Rahmadsyah, Rahmadsyah (Talenta Publisher, 2024)
Research on the effect of of annealing temperature variations on the mechanical properties of AISI 1045 carbon steel has been conducted by varying the annealing temperatures. The samples used in this study had a diameter of 20 mm and a length of 30 mm. Since AISI 1045 steel is very important in the manufacturing industry, extensive research and development. This study aims to analyze the microstructure formed during the annealing process at different temperatures, to determine the impact of annealing temperature on the hardness values of AISI 1045 steel, and to evaluate the corrosion rate of the steel. The samples were heated in a furnace for 1 hour at temperatures of 250°C, 500°C, 750°C, and 1000°C. After removal from the furnace, the samples were returned to room temperature. Subsequently, hardness tests, corrosion rate tests, and microstructural observations were conducted using a Scanning Electron Microscope (SEM). The results indicated that a hardness of 119.3 HRC could be achieved at 500°C, and a corrosion rate of 0.0014 mm/y could be achieved at 1000°C. The values obtained from these tests, supported by the SEM observations, suggest that AISI 1045 carbon steel exhibits good mechanical properties after the annealing process.